Seasonal and daily protandry in a cyprinid fish - Marek Šmejkal (Nature Portfolio, 2017)
Abstract In polygynandrous mating systems, in which females limit reproductive success, males can increase their success by investing in courtship. Earlier arrival at the spawning ground compared to when females arrive may increase their opportunities in competitive mating systems. In this study, we used passive telemetry to test whether a male minnow known as the asp, Leuciscus aspius, times its arrival at spawning grounds relative to the arrival of females. Males arrived in a model stream approximately five days earlier than females on average and left four to five days later than females over two years. Both sexes performed a daily migration between a staging ground (standing water, low energy costs) and the fluvial spawning ground (high energy costs). Fish abundance peaked twice a day, with a major peak at sunset and a minor peak at sunrise and with the evening peak abundance for males occurring 1 hour 40 minutes earlier than that of females. The number of females on the spawning ground never exceeded the number of males. While the degree of protandry is hypothesized to be influenced by the operational sex ratio (ranging from 0.5 to 1 in our study), our data did not support this theory.